Assessing Evaluation Education in African Tertiary Education Institutions: Opportunities and reflections - Dr Tirivanhu, Precious; Dr Chirau, Takunda; Ms Waller, Cara; Mr Robertson, Hanlie (South African Journal of Higher Education, 2018)
The demand for knowledge from evaluations to inform evidence-based policy making continues to rise in Africa. Simultaneously, there is increased recognition of the role tertiary education institutions can play in strengthening evaluation practice through high quality evaluation education. This article investigates the status quo of evaluation education in selected tertiary institutions in Anglophone African countries. The article utilizes a mixed methods research methodology that blends secondary data review, an online survey using a structured questionnaire and two regional workshops. Data was collected from 12 Anglophone African tertiary education institutions. Findings indicate that evaluation education in Anglophone African tertiary institutions is mostly in the nascent stages and there are mixed feelings on the appropriate entry levels (undergraduate or postgraduate). The study highlights the need for developing a specialized evaluation curriculum as evaluation education still borrows from theories and methodologies from the North. Institutional, operational and policy-related challenges are highlighted as well as the potential for collaboration among various stakeholders in strengthening the design and implementation of evaluation education. Key tenets for strengthening evaluation education are highlighted and discussed.
Keywords: Anglophone Africa, evaluation capacity development, evaluation education, monitoring and evaluation, tertiary education institutions